Analisis Bentuk, Pola Pelaksanaan dan Peran ‘Basiru’ dalam Pembangunan Pedesaan di Desa Selante Kabupaten Sumbawa - Sumarlin Sumarlin; Anton Anton; Ismiati Ismiati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
One widely applied strategy for accelerating rural development is the